2020
DOI: 10.3390/app10176112
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Auto-Hydrolysis Process for the Recovery of Antioxidants and Cellulose from Wheat Straw

Abstract: Wheat straw is an easily affordable, cost-effective and natural source of antioxidants and cellulose, but its full potential is not yet utilized. In the present investigation, an auto-hydrolytic process was applied to recover both antioxidant phenolic compounds and cellulose from wheat straw. Two three-step acid/alkaline fractionation processes were applied differing for the first step: a conventional mild acid hydrolysis or an auto-hydrolysis. The liquors from the first step were analyzed for the recovery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…Due to the higher levels of xylose obtained by our approach, we conclude that especially hemicelluloses were more efficiently hydrolyzed from wheat straw steam-exploded in the presence of dH 2 O. Probably the presence of water facilitates autohydrolysis-like processes of hemicelluloses [36] in the early phase of the steam explosion reaction [37][38][39]. Likewise, when impregnated with water, softwood showed enhanced breakdown upon steam explosion with similar severity factors [40].…”
Section: Discussionmentioning
confidence: 93%
“…Due to the higher levels of xylose obtained by our approach, we conclude that especially hemicelluloses were more efficiently hydrolyzed from wheat straw steam-exploded in the presence of dH 2 O. Probably the presence of water facilitates autohydrolysis-like processes of hemicelluloses [36] in the early phase of the steam explosion reaction [37][38][39]. Likewise, when impregnated with water, softwood showed enhanced breakdown upon steam explosion with similar severity factors [40].…”
Section: Discussionmentioning
confidence: 93%
“…The autohydrolysis of agave bagasse at 160 ℃ for 50 min showed that it had a main component as cellulose (35%), followed by lignin (25%) and hemicellulose (6%) [31]. The previous study presented that cellulose (78%), lignin (6%) and hemicellulose (1%) constituted the solid phase of autohydrolyzed wheat straw (at 190℃ for 15 minutes) [43]. It was reported that the xylan content in the solid residues decreases with the increase of the pretreatment temperature [17,19].…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the chemical composition of the spent solid recovered in the autohydrolysis of melon peels at 140 °C, it would be plausible to implement a second autohydrolysis step to obtain a solid fraction enriched in cellulose with potential applications, and a liquid fraction with a higher phenolic content [ 78 ]. For instance, this cellulose would be suitable for the biotechnological production of fermentable sugars, or for the production of nanocellulose [ 13 ].…”
Section: Resultsmentioning
confidence: 99%